An Nphp1 knockout mouse model targeting exon 2–20 demonstrates characteristic phenotypes of human nephronophthisis. Issue 2 (20th August 2021) - Li, Dantong; Hu, Miaoyue; Chen, Huamu; Wu, Xiaohong; Wei, Xiaoya; Lin, Hongrong; Gao, Xuefei; Wang, Haiyan; Li, Min; Ong, Albert C M; Yue, Zhihui; Sun, Liangzhong
Abstract: Nephronophthisis (NPH) is the most prevalent monogenetic disorder leading to end-stage renal failure (ESRD) in childhood. Mutations in Nphp1, encoding a cilia-localized protein, account for the majority of NPH cases. Despite its identification many years ago, Nphp1 deletions targeting exon 4 or exon 20 have not reproduced the histological features of human NPH in murine models. In this study, we deleted exon 2–20 of Nphp1 by CRISPR/Cas9 gene editing to create a near-total knockout (KO) mouse model ( Nphp1 del2–20/del2–20 ). Nphp1 del2–20/del2–20 mice faithfully reproduced the renal and extrarenal phenotypes associated with human NPH, including renal cyst development, tubular basement membrane thickening, retinal degeneration and abnormal spermatogenesis. Importantly, Nphp1 re-expression using an adenoviral-associated-virus-9 vector could partially rescue both renal and retinal phenotypes in Nphp1 del2–20/del2–20 mice. Our results reported the first relevant Nphp1 mouse model with renal phenotypes for human disease. It will be a valuable model for future studies of Nphp1 function and to develop novel treatments for this common childhood disease.